(untitled) (Research, Society and Development, 2024)
This study aimed to investigate the effect of Mozart’s Sonata K448 on relapse after fear memory extinction in female mice with dysbiosis. A total of eight pregnant mice were used, and their female offspring were divided into two groups: G1 (Mozart, N = 8) and G2 (Control, N = 8). The mice were exposed to the corresponding music from 9:00 PM to 7:00 AM, from the intrauterine period until euthanasia. The methodology included a Habituation Test, Aversive Training, and Memory Extinction Test, with all procedures being recorded on video. The data obtained were analyzed using the Student’s t-test for training and ANOVA for the tests, with a significance level set at p ≤ 0.05. The results showed no significant difference between the groups in the recall test (t(14) = 0.379; p = 0.710). The mean ± standard error of the mean for the Mozart group was 3.09% ± 0.88%, while for the Control group it was 2.69% ± 0.57%. It is concluded that exposure to Mozart’s Sonata K448 did not have a significant impact on fear memory relapse in mice, contrasting with previous research suggesting benefits of music on memory.